2014
DOI: 10.1007/s00330-014-3366-8
|View full text |Cite
|
Sign up to set email alerts
|

Elastography ultrasound for breast lesions: fat-to-lesion strain ratio vs gland-to-lesion strain ratio

Abstract: FLR was higher than GLR in both malignant and benign breast lesions. Both FLR and GLR were higher in malignant than in benign breast lesions. FLR yielded better diagnostic performance than GLR in breast lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 40 publications
6
34
0
Order By: Relevance
“…The strain ratio and elastography assessed with a 5‐point scale have been used in breast imaging . In a study comparing these metrics for diagnosis of benign and malignant breast lesions, the strain ratio showed better diagnostic performance than elastography; this finding was similar to ours.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The strain ratio and elastography assessed with a 5‐point scale have been used in breast imaging . In a study comparing these metrics for diagnosis of benign and malignant breast lesions, the strain ratio showed better diagnostic performance than elastography; this finding was similar to ours.…”
Section: Discussionsupporting
confidence: 84%
“…The strain ratio and elastography assessed with a 5-point scale have been used in breast imaging. 16 In a study comparing these metrics for diagnosis of benign and malignant breast lesions, the strain ratio showed better diagnostic performance than elastography 17 ; this finding was similar to ours. Elasticity scores evaluate target lesions qualitatively with visual analysis by reviewers and might be influenced by many subjective factors.…”
Section: Discussionsupporting
confidence: 84%
“…Zhou et al 26. reported that fatty tissue was more stable than breast glandular tissue because fatty tissue is influenced little by the factors such as menstrual cycle, sex hormones and duration period.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern corresponds to an Italian elastosonographic score of 3 or 4 [6]. This appearance may depend on the amount of fibrous tissue present in hamartomas; in fact, the different tissues that make up the breast have distinct elastographic features, with fibrous and glandular tissues displaying greater stiffness than fat tissue [7,8] (Figs. 4, 5, 6).…”
Section: Us Appearancementioning
confidence: 99%